Exploring the effect of zakat on wealth redistribution in Morocco Using agent-based modeling - Abderrahim, Haddad; Fadma, El Mosaid (Journal of Islamic, Social, Economics and Development, 2025)
Zakat is one of the pillars of Islam, a mandatory financial obligation for Muslims who meet specific conditions. Its significance lies in its role in wealth redistribution and reducing economic disparities between the rich and the poor. This contribution, often referred to as an "Islamic tax," is intended to provide for the immediate needs of specific social groups, as defined in verse 60 of Surah At-Tawba in the Holy Quran. Globally, wealth distribution generally follows Pareto's law, which explains its concentration among a small percentage of individuals. One way to mitigate this inequality is through taxation. In Islamic finance, Zakat is presented as a mechanism for poverty alleviation and economic redistribution. This study proposes an agent-based modeling (ABM) approach using NetLogo software (version 6.4p), based on the framework developed by Wilensky. Within this model, we incorporate the concept of Zakat to analyze its impact on wealth distribution. The results of the simulation, assessed through various indicators, will then be presented and discussed.